Nosocomial Outbreak of SARS-CoV-2 in a Non-COVID Zone of a Tertiary Care Hospital of North India: Need to Upgrade Infection Control Practices - Kirtan Rana; Bhawna Sharma; Pinnaka Venkata Maha Lakshmi; ManharPreet Kaur; Mini P. Singh; Ranjana Singh; Sameer Aggarwal; Manisha Biswal (SAGE Publishing, 2021)
Background Hospital acquired infections are preventable cause for morbidity and mortality worldwide. In the current pandemic era proper implementation of infection control measures can prevent the spread of such infections including SARS-CoV 2. The study was done to identified the source and reason for spread of COVID-19 infection and devise recommendations to halt the progress of infection in a non-COVID area. Methods An outbreak in a non-COVID area of a tertiary care hospital was investigated by the infection control team along with the epidemiologist when they were notified about the rising cases of COVID-19 from Advanced Trauma Center's (ATC) disaster ward. The time, place and person distribution of the cases were studied. Recommendations based on gaps identified were developed onsite and implemented to control the outbreak. Results The outbreak lasted from 19th December 2020 to 12th January 2021, affecting 34 people (25 patients and 9 health care workers). The attack rate was 9.2%. We identified the causes of current outbreak as compromises in infection prevention measures, high bed patient ratio, irregularities in the ventilation system, overcrowding by patient attendants and communication gaps between nursing officers and doctors. Measures required to control the outbreak were implemented and no cases were reported for 2 weeks following the last positive case. Conclusion Non-COVID areas of hospitals are also at risk of nosocomial outbreaks of SARS-CoV 2 and therefore strict infection prevention measures those designated to COVID areas should be followed in non-COVID zones also to prevent such outbreaks.